100 years of modelling ligand–receptor binding and response: A focus on GPCRs. (28th February 2020) - Finlay, David B.; Duffull, Stephen B.; Glass, Michelle
Abstract : Experimental pharmacologists rely on the application of models to describe biological observations in order to learn about a drug's effective concentration, the strength with which it binds its target and drives a response (at either molecular or system level), and the nature of more complex drug actions (allosterism/functional selectivity). Models in current use build upon decades of basic principles, going back to the beginning of the last century. Yet often, researchers are only partially familiar with these underlying principles, creating the potential for confusion due to failure to recognise the underpinning assumptions of the models that are used. Here, we describe the history of receptor theory as it underpins receptor stimulus–response models in use today, emphasising particularly attributes and models relevant to GPCRs—and point to some current aims of model development.